Pengembangan Soygurt Berbasis Isolat Protein Kedelai dengan Penambahan Whey Tahu sebagai Inovasi Pangan Fermentasi: The Development of Science and Technology in the Field of Food Has Driven the Emergence of Various Innovations in the Composition of Functional Food Products - Nicky, Dhea; Bintari, Siti Harnina (Jurnal Ilmiah Pangan Halal, 2025)
This research aims to develop a soygurt formulation based on soy protein isolate with the addition of tofu whey and to analyze the resulting physicochemical and organoleptic characteristics. Soy whey contains nutrients such as dissolved proteins, simple sugars, and minerals, which have the potential to support the fermentation process. The research was conducted experimentally on a household scale using four treatments of tofu whey concentration, namely 0%, 10%, 20%, and 30%. The parameters observed included pH value, total acidity, visual viscosity, and sensory evaluation of taste, aroma, texture, color, and overall impression by 25 respondents. The results show that the addition of tofu whey lowers the pH and increases the total acidity as the concentration of whey increases. The viscosity level also increases, especially at concentrations of 20–30%. The formulation with 20% tofu whey produced the best organoleptic balance, with the highest scores in taste, aroma, texture, and overall impression. These results indicate that tofu whey has the potential to be used as an additive in the development of plant-based fermented products, while also supporting the utilization of tofu whey waste into practical and functional food products.